Sestrin3 confers resistance to recombinant human arginase in small cell lung cancer by activating Akt/mTOR/ASS1 axis - Zhongqiang Zhang; Zizhe Lin; Weishan Li; Binxiong Chen; Yueming Liu; Hanchao Gao; Shi Xu (PLoS ONE, 2025)
Drug resistance is a major obstacle in the clinical management of small cell lung cancer (SCLC), we have proved the promising anticancer effect of recombinant human arginase (rhArg, BCT-100) in SCLC in vitro and in vivo . In order to promote the clinical application of recombinant human arginase, it is necessary to explore the underlying resistant mechanisms of BCT-100 in SCLC. Here, we cultured and obtained the acquired drug-resistant SCLC cell line (H446-BR), which displayed different cellular phenotypes (enhanced migration ability) compared with the parental cell line (H446). sestrin3 (SESN3) was confirmed with high expression in resistant cell line. Knockdown SESN3 could re-sensitize resistant cells to BCT-100 treatment and reverse the aggressive feature of H446-BR. The Akt-mTOR signal pathway and ASS1, which were highly expressed in resistant cells, were down-regulated after silencing SESN3. MK-2206 and rapamycin suppressed the expression of ASS1 in H446-BR cell. In xenograft model, BCT-100 has little anti-tumor effect on H446-BR compared with H446 as well as H446-BR silenced sestrin3. Collectively, these results elucidate SESN3 plays an essential role in resistant mechanism, which will provide a valuable source of information for translational research.